User testing of a hypospadias decision aid prototype at a pediatric medical conference. Issue 5 (October 2020) - Chan, Katherine H.; Misseri, Rosalia; Carroll, Aaron; Frankel, Richard M.; Moore, Courtney; Cockrum, Brandon; Wiehe, Sarah
Summary: Introduction: Based on our previous qualitative work, we created a web-based decision aid (DA) prototype to facilitate shared decision-making regarding hypospadias. Objective: The objective of this study was to obtain rapid feedback on the prototype as part of an iterative, human-centered design process. Methods: We conducted this study at a statewide, pediatric educational conference in May 2019, recruiting attendees by verbal/written announcements. The DA consisted of: hypospadias overview and surgery "storyboard, " frequently asked questions, parent testimonials, and a values clarification exercise. Participants viewed the DA on a tablet as they participated in semi-structured, qualitative interviews covering website acceptability, usability, and preference for surgical photographs versus illustrations. Three coders used qualitative content analysis to identify themes and resolved disagreements by consensus. Results: Of 295 conference attendees, all 50 who approached us agreed to participate. Responses from 49 participants were available for analysis: 67% female, ages 20–69, 65% Caucasian, 55% MDs. 96% of participants thought the website design matched its purpose; 59.1% preferred surgical illustrations, 8.2% preferred photos, 30.6% preferred both and 2.0% did not like either. Participants recommended improvements in: a) usability/accessibility (e.g. site navigation, visual layout, page length), b) content coverage (e.g. epidemiology, consequences of no/delayed surgery, lifelong risks), c) parent-centeredness (e.g. reading level/writing style) and d) implementation (provider tools, printable handouts). The Extended Summary Figure shows a revised image of the first step of a hypospadias repair based on feedback about participants' preferences for illustrations rather than photographs. Discussion: The main strength of our study was the valuable feedback we obtained to inform critical revisions of the DA prototype. We also demonstrated the feasibility and efficacy of a conducting a usability evaluation of a web-based DA in a medical conference setting. One limitation of this study is that the relatively small population sampled limits generalizability and our findings may not reflect the views of all providers who care for hypospadias patients. Conclusions: The vast majority of providers thought that the design of the Hypospadias Homepage matched its purpose and most preferred surgical illustrations rather than photos to demonstrate the steps of hypospadias surgery. Based on their feedback, we plan to focus our efforts in the following areas: 1) improvement of navigation/menus, 2) reduction in the amount of text per page, 3) expansion of specific content coverage and 4) inclusion of "parent-friendly" visuals such as infographics to represent quantitative data and colorful illustrations to depict hypospadias and its surgical repair. Extended Summary Figure LEFT: Depiction of surgery step 1 before the pediatric medical conference depicting a black-and-white illustration of dorsal plication and its corresponding surgical photographs with a needle in the glans. RIGHT: Revised surgery step 1 after feedback from the pediatric medical conference depicting a colorful, cartoon-like illustration of dorsal plication with no needle. Extended Summary Figure